$ABCD$, $AEFG$, $GHIJ$ are squares; $ABCD$ is inscribed in the semicircle, and $E$ is the middle of $[AD]$. Attention! $JG+GA+AO \neq r$. We have to find the areas of the squares.


It's easy to find that $Area(ABCD)=\frac{4r^2}{5}$ and $Area(AEFG)=\frac{r^2}{5}$, but I can't figure out how to find the area of the last square. Can you help me? Thanks!

  • $\begingroup$ y coord of I = h; x coordinate is OA+AG+h; Pythagoras can be now applied. $\endgroup$ – Narasimham Jun 5 '18 at 0:58


The first square can be found by the condition

  • $\sqrt{r^2-x^2}=2x\implies r^2-x^2=4x^2 \implies x_D=\frac r {\sqrt 5}\implies A_1=(2x_D)^2=\frac45r^2$

For the second we have

  • $\sqrt{r^2-x^2}=x-x_D$ from which we can obtain $x_F$ and then $A_2=(x_F-x_D)^2$

For the third we have

  • $\sqrt{r^2-x^2}=x-x_F$ from which we can obtain $x_I$ and then $A_3=(x_I-x_F)^2$
  • $\begingroup$ I'm not sure what you mean by $\implies$ in the second and third statements. $\endgroup$ – saulspatz Jun 4 '18 at 20:23
  • $\begingroup$ @saulspatz it stands for "from which we can obtain..." $\endgroup$ – user Jun 4 '18 at 20:23
  • $\begingroup$ So obvious... I did not notice that $OI=r$. Thanks! $\endgroup$ – Iulian Oleniuc Jun 4 '18 at 20:24
  • $\begingroup$ @IulianOleniuc You are welcome! Bye $\endgroup$ – user Jun 4 '18 at 20:27
  • $\begingroup$ @saulspatz You are welcome! I've changed the notation to be more clear. Thanks $\endgroup$ – user Jun 4 '18 at 20:27

Let's let the radius of the circle be $1$ for a while and account for $r$ at the end. I'm also flipping your circle so that all of the interesting stuff happens in the first quadrant.

enter image description here

Consider the vertical line $x= x_i$. To build a square to the left of that with sides of length $s_i$, the upper right corner of that square will have coordinates of $(x_i+s_i, s_i)$ and will be on the unit circle. Hence

\begin{align} (x_i + s_i)^2 + s_i^2 &= 1 \\ 2s_i^2 + 2 x_i s_i - (1-x_i^2) &= 0 \\ s_i &= \dfrac{-2x_i + \sqrt{4 x_i^2 + 8 - 8 x_i^2}}{4} \\ s_i &= \dfrac{\sqrt{2 - x_i^2} - x_i}{2} \\ x_{i+1} &= \dfrac{\sqrt{2 - x_i^2} + x_i}{2} \\ \end{align}

If we start with $x_1 = \dfrac{1}{\sqrt 5}$

Then $s_2= \dfrac{1}{\sqrt 5}$ and $x_2 = \dfrac{2}{\sqrt 5}$

$s_3= \dfrac{\sqrt 6 - 2}{2\sqrt 5}$ and $x_3 = \dfrac{\sqrt 6 + 2}{2\sqrt 5}$

$s_4= \dfrac{2+\sqrt 6 - \sqrt{30-4 \sqrt 6}}{4\sqrt 5}$ and $x_4 = \dfrac{2+\sqrt 6 + \sqrt{30-4 \sqrt 6}}{4\sqrt 5}$

and so on


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.